2016
DOI: 10.1089/ten.tec.2015.0187
|View full text |Cite
|
Sign up to set email alerts
|

A New Rat Model for Translational Research in Bone Regeneration

Abstract: The European Union (EU) directive 2010/63/EU on the protection of animals used for scientific purpose focused on reducing the number of animals and refinement of breeding. Animal studies are necessary to protect human health. Lots of animal models exist to study bone regeneration, but a reliable, well reproducible, and relatively inexpensive model with the possibility for multiple testing in the same animal is still missing. Rats may serve as good models for this due to the small animal size and good cost/bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…CS and EC, as the shell material of microcapsules, are not cytotoxic and degradable and can therefore promote cell proliferation . The main histological findings in our study revealed significant degradation of the microcapsules, especially in the period from 4 to 12 weeks, whereas the Bio‐oss was only slightly degraded at 4 weeks after surgery and showed no obvious further degradation at 12 weeks after surgery, which is consistent with previous reports . Moreover, the drug release from the CS‐EC@Ca microcapsules is steady and sustained for osteogenesis, and with inner drug release, a perforated channel structure is formed, which is conducive to cell adhesion and proliferation .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…CS and EC, as the shell material of microcapsules, are not cytotoxic and degradable and can therefore promote cell proliferation . The main histological findings in our study revealed significant degradation of the microcapsules, especially in the period from 4 to 12 weeks, whereas the Bio‐oss was only slightly degraded at 4 weeks after surgery and showed no obvious further degradation at 12 weeks after surgery, which is consistent with previous reports . Moreover, the drug release from the CS‐EC@Ca microcapsules is steady and sustained for osteogenesis, and with inner drug release, a perforated channel structure is formed, which is conducive to cell adhesion and proliferation .…”
Section: Discussionsupporting
confidence: 90%
“…28,29 The main histological findings in our study revealed significant degradation of the microcapsules, especially in the period from 4 to 12 weeks, whereas the Bio-oss was only slightly degraded at 4 weeks after surgery and showed no obvious further degradation at 12 weeks after surgery, which is consistent with previous reports. 30 Moreover, the drug release from the CS-EC@Ca microcapsules is steady and sustained for osteogenesis, and with inner drug release, a perforated channel structure is formed, which is conducive to cell adhesion and proliferation. 14 Bio-Oss, on the other hand, degrades slowly and remains even 11 years after implantation, which hampers further bone formation and full regeneration in those areas.…”
Section: Discussionmentioning
confidence: 99%
“…It was first described by M. L. Wang, Massie, Perry, Garfin, and Kim (2007) for analyzing the impact of bone loading in osteoporotic animals. It was introduced to dentistry in 2016 by Renaud et al (2016) and further described by Farkasdi et al (2018). It may be questioned to what extent residual growth of the rat vertebrae had an impact on the findings of the present investigation.…”
Section: Stimulation Of Bone Remodeling By Compressive Forces Has Beenmentioning
confidence: 88%
“…It was first described by M. L. Wang, Massie, Perry, Garfin, and Kim () for analyzing the impact of bone loading in osteoporotic animals. It was introduced to dentistry in 2016 by Renaud et al () and further described by Farkasdi et al (). A big advantage of this animal model is the relative ease of interoperative accessibility, and, due to the small size of the tail, high‐resolution μCT images can be obtained from living animals.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the attenuation of the rays of titanium repair, it will result in some pseudo shadow in the CT and X-ray image. HM Li and others utilized electron spin resonance to study free radical attenuation of PEEK and discovered that there's no radical 20 min after radiation (600 kGray) on PEEK, so PEEK was not considered a secondary radiation source after gamma-ray sterilization [19,20]. PEEK has outstanding advantages on the biocompatibility, no toxin, no immunity, no allergens.…”
Section: Discussionmentioning
confidence: 99%